Current opinion on maximizing veterinary profession growth and contributions - NIMMANAPALLI, R; DONAPATY, S R (The Indian Journal of Animal Sciences, 2016)
Veterinary profession sphere overlaps three major biology arenas namely agriculture, basic sciences, and human medicine. Thus, so far the investments in veterinary field are not proportional to the scope of their responsibilities. Rededication and rejuvenation can help veterinary profession to maximize outcomes in poverty alleviation, food security, environmental protection, integrated zoonotic disease prevention and control, integrated public services delivery, animal welfare and human-animal bond. Transforming backyard farming into farm management; symptomatic treatment philosophy into prevention and control ethos; one medicine, require capacity building, continuing education as well as curriculum reforms. Consensus needs to be built within the profession to enrol stakeholder participation in professional growth and outcomes enhancement. In this article, authors used developed world experience to suggest a customized reform and manpower empowerment approach for increasing veterinary profession stature and contributions for India. It is hoped that awareness brought forward to elevate discussion on veterinary profession opportunities would be beneficial to the profession as well as to the society.